Studi Perbandingan Algoritma Blind Equalization Dengan Metode Dekomposisi Pada Blind Equalizer - Fitri Amillia (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
Problems inter symbol interference (ISI) disturb in acceptance thus reducing efficiency transmission digital. ISI can be overcome by design an receiver furnished with equalizer. Analysis result simulation system as basic substantiation any increase performance of telecommunication system. A system of tested use the blind equalizer with blind equalization algorithm a method of the decomposition of the rate of the convergence chart mean square error. Performance testing of 16 QAM system with BER that is 10-3 retrieved value of Eb/No = 10.58 dB for free ISI and the value of Eb/No = 17.6 dB for systems with ISI obtained difference between Eb/No of 7.02 dB. So the system suffered losses of power 7.02 dB. Simulation results of convergence rate of mean square error decomposition method using Sato algorithm faster convergence rate compared to the mean square error decomposition method using CMA.Keywords: blind equalization algorithm, computational complexity.